Relationship between plasma high-sensitivity C-reactive protein and traditional cardiovascular risk factors among active-duty military personnel in the Republic of Serbia - Ratković , Nenad; Pandrc, Milena; Perić, Vitomir; Stojanović, Maja; Rančić, Nemanja (Vojnosanitetski pregled, 2022)
Background/Aim. Approximately one-third of individuals with only one cardiovascular (CV) risk factor or without any, as well as 40% of individuals with a concentration of cholesterol less than average, die from CV diseases (CVD). Recent studies underlined the significant role of inflammation in atherosclerosis and its complications. The aim of this study was to analyze the association of high-sensitivity C-reactive protein (hs-CRP) with traditional risk factors for coronary heart disease. This is the first such study in Serbia. Methods. This is an observational cross-sectional study, which included active-duty military personnel of similar socio-epidemiological and economic characteristics. Plasma hs-CRP and traditional CV risk factors were evaluated. The relative CV risk was staged as low (hs-CRP < 1 mg/L), intermediate (hs-CRP between 1 and 3 mg/L), and high (hs-CRP > 3 mg/L). The Systematic Coronary Risk Evaluation (SCORE) system was used for absolute CV risk assessment and total risk (fatal and non-fatal events). Results. The study included 205 participants, average age of 39 (35–43) years, with median and interquartile range values of hs-CRP 0.80 mg/L (0.43–1.75 mg/L), with average hs-CRP values of 0.71 mg/L in participants younger than 40 years of age and 1.2 mg/L in the older than 40 years. The difference in hs-CRP values between these two groups was statistically significant (p = 0.006). There was a significant positive correlation between hs-CRP and age (r = 0.266, p < 0.001), weight (r = 0.223, p = 0.001), body mass index (BMI) (r = 0.344, p < 0.001), diastolic hypertension (r = 0.190, p = 0.007), LDL cholesterol (r = 0.152, p = 0.032), triglycerides (r = 0.144, p = 0.039), number of risk factors (r = 0.210, p < 0.003), as well as negative correlation with HDL cholesterol concentration (r = -0.148, p < 0.035). There was no significant correlation between hs-CRP concentration and total cholesterol (r = 0.131, p = 0.062). According to hs-CRP values, high CVD risk was found in 17.7% of participants older than 40 years of age, and based on SCORE system staging, 90% of participants have intermediate CVD risk. The results of stepwise multiple regression analyses showed that BMI was independently associated with an hs-CRP concentration in the group younger than 40 years of age. Among the older participants, age was found to be associated with concentration of fibrinogen. Conclusion. In the population of active military personnel in the Republic of Serbia, hs-CRP is correlated with some of the risk factors for CVD, and only BMI is independently correlated with hs-CRP in those under 40 years of age. Levels of plasma hs-CRP are increased with aging, implying that hs-CRP measurement may provide a more accurate assessment of the individual overall risk profile for CVD in the Serbian military personnel population.